Public perception of COVID-19 vaccination in Banjar District, Indonesia: the role of sociodemographic factors - Mardiati, Nurul; Mersa, Lina; Torizellia, Cast (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov-2) virus. Vaccination is one way to prevent the spread of the COVID-19 virus. One of the factors causing the low acceptance of COVID-19 vaccination in the community is the perception of COVID-19 vaccination. Socio-demographic factors such as age, gender, occupation, last degree of education, and monthly income have a substantial relationship with public perceptions of COVID-19 vaccination. The purpose of this study was to analyze public perceptions of COVID-19 vaccination. This study used an analytical observational method with a cross-sectional study design. The sample in this study used a consecutive sampling technique, totaling 400 people. The majority of respondents had a enough good perception of COVID-19 vaccination. There is a relationship between socio-demographic factors of age, occupation, last degree of education, and monthly income with people's perceptions of COVID-19.